The influence of the work environment and competence on employee performance mediated by the motivation of the case study work on special waroeng sambal "SS" in Yogyakarta - Awanda Nurwati (JURNAL STUDI MANAJEMEN ORGANISASI, 2019)
This study aims to obtain empirical evidence about the influence of the work environment and competence mediated by work motivation on Waroeng Special Sambal "SS" in Yogyakart. The independent variables used are work environment and competence. The dependent variable used is the performance of Waroeng Special Sambal "SS" employees in Yogyakarta. And work motivation as a mediating variable. The population in this study were all employees of Waroeng Special Sambal "SS" in Yogyakarta. Samples collected using simple random sampling in Waroeng Special Sambal "SS" in three branches namely East Babarsari Branch, Perumnas Branch and Samirono Branch with 108 respondents. The method of analysis in this study uses a partial least square (PLS) method with 2 models, namely the outer model and the inner model.The results of this study indicate that there is a significant positive influence between work environment on the performance of Waroeng Special Sambal "SS" employees, significant positive between competencies on the performance of Waroeng Special Sambal "SS" employees, positive influence between work environment on the performance of Waroeng Special Sambal "SS" employees mediated by work motivation, a positive influence between competence on the performance of Waroeng Special Sambal "SS" mediated by work motivation. This study shows the direct and indirect effects between variables. Significant positive direct effect between work environment, competence and work motivation of Waroeng Special Sambal "SS" in Yogyakarta.Keywords: Work Environment, Competence, Work Motivation, Employee Performance.